2017
DOI: 10.17770/sie2017vol3.2241
|View full text |Cite
|
Sign up to set email alerts
|

Primary School Teachers’ Approach to Advantages of Ict Use in Education

Abstract: The article reveals primary school teachers’ approach towards advantages and disadvantages of information and communication technologies, their influence to children education as well as teacher experience in the application of ICT technologies in primary education and opportunities of teachers in the development of professional competence. Qualitative study (structured interview) was carried out which involved the teachers of 1 – 4 forms more than four years actively using ICT in the classroom. According to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The early or parallel active involvement of parents in literacy processes seems to determine the convergent or divergent evaluation of the importance of kindergarten goals, the establishment of a common and mutually valued framework of communication and educational action for the benefit of students (Tsirmpa et al, 2021). In addition, since a positive relationship between literacy using digital tools (Neumann, 2014), and the use of Information and Communication Technology in promoting pupils' learning (Braslauskiene et al, 2017), has been identified, the assessment of the usefulness of digital literacy by teachers and parents seems to be an important parameter, especially in the distance learning process, where parents assume a complex teacher-guide and parental role (Garbe et al, 2020;Lau & Lee, 2020).…”
Section: Parentsmentioning
confidence: 99%
“…The early or parallel active involvement of parents in literacy processes seems to determine the convergent or divergent evaluation of the importance of kindergarten goals, the establishment of a common and mutually valued framework of communication and educational action for the benefit of students (Tsirmpa et al, 2021). In addition, since a positive relationship between literacy using digital tools (Neumann, 2014), and the use of Information and Communication Technology in promoting pupils' learning (Braslauskiene et al, 2017), has been identified, the assessment of the usefulness of digital literacy by teachers and parents seems to be an important parameter, especially in the distance learning process, where parents assume a complex teacher-guide and parental role (Garbe et al, 2020;Lau & Lee, 2020).…”
Section: Parentsmentioning
confidence: 99%
“…According to Falloon (2020), "digital skills" are the abilities needed to use digital tools, programs, and platforms successfully. These abilities include a spectrum of competencies, from simple ones like operating a computer or smartphone (Braslauskienė et al, 2017;Huda et al, 2018) to more complex ones like programming or digital marketing (Chen et al, 2017;Kumara, 2020). On the other hand, ICTC is a larger notion that covers both digital skills and an awareness of how to use digital technology ethically and successfully in a range of situations, including the workplace, classroom, and daily life (McGarr & McDonagh, 2021;Tondeur et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Also, ICT includes technological tools such as computers, software, networks, and the Internet. These tools and technologies are used to meet, accelerate, and optimize the information and communication needs of individuals and institutions (Braslauskienė et al, 2017). These technologies play an important role in every aspect of our lives by providing effective and efficient solutions in various fields from education to health, from business to communication (Chen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There are several advantages to the use of ICT in the educational setting. These advantages include making learning more interesting and interactive for students (Adam & Ray, 2020;Braslauskienė et al, 2017); provide more effective learning opportunities to students with special needs (Istenic Starcic & Bagon, 2014;Mallidis-Malessas et al, 2022); enabling more efficient completion of homework and group work (Agasisti et al, 2020;Melander Bowden & Svahn, 2020); being a versatile tool for teachers with its ability to be used in different courses (Baez Zarabanda, 2019); helping teachers identify and address the specific needs of their students and improve teachers' professional competencies by using various ICT tools in the classroom (Braslauskienė et al, 2017;Ocampo-Botello et al, 2019). Overall, the use of ICT in education can lead to more effective and efficient teaching and learning processes and better prepare students for the digital world they will encounter in their future careers (Braslauskienė et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation